Cooperation of BIBB with international partners - Kissling, Hans-Joachim [Verfasser] (My University, 2007)
"Exchanging experience across national boarders is of ever increasing importance, especially in the field of vocational education and training (VET), considering the challenges posed by globalisation. In keeping with its legal remit, the German Federal Institute for Vocational Education and Training (BIBB) cooperates with VET institutions around the world. The current focal areas of BIBB's international work are projects relating to comparative and transfer research, involvement in the process of European VET policy, and advisory services for the international education market. This article begins by looking at the position of BIBB in the international context, and goes on to report on a partners' meeting convened by BIBB and attended by 16 VET institutions from various countries in Europe. This provided a host of opportunities for exchanging views on current issues in European VET." (BIBB)
Keywords: S 3.5.2.2 Bundesinstitut für Berufsbildung (BIBB); I 1 Internationale Berufsbildung; Bundesinstitut für Berufsbildung; Internationale Zusammenarbeit; Berufsbildung; Europäische Union